Angiotensin-Converting Enzyme Activity in Patients with Pneumonia and COPD: Clinical Evaluation and Diagnostic Value - Capri R. Reed (Open Journal of Physicians and Surgeons, 2026)
Acute pneumonia and chronic obstructive pulmonary diseases (COPD) occupy a significant place in the clinical presentation of internal medicine. In the overall structure of respiratory diseases, the combined share of these pathologies is more than % . By now the pathophysiological basis for the development of pneumonia and COPD has been elucidated and their clinical presentation has been comprehensively studied. However, it is still not clear how the disease affects the production of some key humoral regulators by the lungs . At the same time the absence of biochemical methods for monitoring pathological changes in lung tissue in clinical practice is noteworthy . These two problems are closely interrelated. Obviously biologically active substances the synthesis of which is ensured primarily by lung tissue can indicate its condition. A prerequisite for the use of such tests in clinical laboratory diagnostics is their technological accessibility. The study of angiotensin-converting enzyme (ACE) in pneumonia and COPD is dictated by the following premises: It is known that the main localization of ACE is the endothelium of the vascular wall . Being richly vascularized the lungs have a huge area of the endothelial surface . Therefore, the lung tissue contains many times more ACE than other organs . It has been established that the lungs serve as the main source of ACE in the human body . Therefore, ACE can be considered as an organ-specific enzyme the activity of which in the blood serum is determined by the morphological or functional integrity of the producing organ. This approach allows us to evaluate the diagnostic significance of ACE for clinical pulmonology. To date a large amount of data has been accumulated on changes in ACE activity in various diseases . However, despite the fact that the problem has been studied studies of ACE activity in acute pneumonia are limited to isolated observations . Information on changes in ACE activity in COPD is incomplete and very contradictory . ACE links the renin-angiotensin and kallikrein-kinin systems being the central link in the regulation of blood pressure . It is known that acute pneumonia is characterized by a decrease in blood pressure . Until now this has been explained by the development of infectious toxic shock . The clinical picture of COPD on the contrary is accompanied by the development of pulmonogenic arterial hypertension the pathogenesis of which still remains unclear . Our objective is to evaluate the clinical diagnostic value of determining ACE activity in blood serum and bronchoalveolar contents in patients with pneumonia and COPD.